KONSEP PENATAAN PERMUKIMAN KUMUH TEPIAN SUNGAI DI KELURAHAN SUNGAI BILU KOTA BANJARMASIN - Syaiful Rahman; Ira Mentayani; Rusmilyansari Rusmilyasari; Emmy Sri Mahreda (Universitas Lambung Mangkurat, 2019)
The uncontrolled condition of settlements on the banks of the river city of Banjarmasin has made the settlements of the river banks as slums. Almost all river banks in each kelurahan are categorized as slums so that the actual river banks can be assets of the city of Banjarmasin, on the contrary, it is a bad face for the city. The program and arranging of structural slums in the river bank settlements in Kelurahan Sungai Bilu have indeed been carried out, but basically, they have not been successfully managed completely. Identification of the characteristics of riverbank slum settlements needs to be done to find out the aspects and variables that affect the slum of riverbank settlements to then formulate an appropriate arranging concept and can be implemented in riverbank slum settlements in the study location. Data analysis in identifying the characteristics of riverbank slum settlements is by presenting tabulated data on the results of a statistical questionnaire completed with mapping and field documentation and through narrative exposure. The theory triangulation analysis is used to formulate the concept of arranging suitable riverbank slum settlements and can be carried out at the research location. The results were obtained for the characteristics of slum settlements and the concept of arranging slum areas in the river banks in Kelurahan Sungai Bilu are arranging in aspects of the function and form of residential building mass, arranging environmental infrastructure, arranging environmental utility systems, arranging public and social facilities, and arranging on non-physical aspects.